2012
DOI: 10.1177/1078390312466918
|View full text |Cite
|
Sign up to set email alerts
|

How Parents Make Decisions to Use Medication to Treat Their Child’s ADHD

Abstract: Interventions to support and guide parents throughout the decisional process are critical to meet the needs of families of children with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…Decisions relating to prescribing methylphenidate in ADHD, and when to suspend or cease medication, are influenced by a range of individuals involved in raising, providing care for and teaching children/adolescents with ADHD – as well as the patients themselves as they become able to actively participate in the decision‐making process. Participants in this study described many ways in which methylphenidate improved the behaviour of the child, echoing reports in a number of other studies (Brinkman et al., ; Bussing & Gary, ; Cormier, ; Hansen & Hansen, ); the need to increase dose to maintain improvements in the longer term was also discussed in this study, in line with the MTA study that reported a 41% increase in the average total daily dose with long‐term treatment (Molina et al., ). Previous studies, as well as the current investigation, highlight the reality that many children have, at one time or another, experienced reduced appetite and difficulties in sleeping as well as suffered from psychological side‐effects in response to methylphenidate (Hansen & Hansen, ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Decisions relating to prescribing methylphenidate in ADHD, and when to suspend or cease medication, are influenced by a range of individuals involved in raising, providing care for and teaching children/adolescents with ADHD – as well as the patients themselves as they become able to actively participate in the decision‐making process. Participants in this study described many ways in which methylphenidate improved the behaviour of the child, echoing reports in a number of other studies (Brinkman et al., ; Bussing & Gary, ; Cormier, ; Hansen & Hansen, ); the need to increase dose to maintain improvements in the longer term was also discussed in this study, in line with the MTA study that reported a 41% increase in the average total daily dose with long‐term treatment (Molina et al., ). Previous studies, as well as the current investigation, highlight the reality that many children have, at one time or another, experienced reduced appetite and difficulties in sleeping as well as suffered from psychological side‐effects in response to methylphenidate (Hansen & Hansen, ).…”
Section: Discussionsupporting
confidence: 82%
“…Stimulant medications or atomoxetine are used and are effective in reducing the symptoms of ADHD and allowing children to focus on academic work (Hechtman et al., ). Parents tend to continue drug treatment long term, in a process described as ‘doing what helps most’ (Cormier, ). This is despite the findings of an 8‐year prospective follow‐up of children treated for ADHD in a multisite study (MTA – Multimodal Treatment of Attention Deficit Hyperactivity Disorder) which did not show any long‐term advantage of medication beyond 2 years in most cases (Molina et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Feelings of ineffectiveness are common, as the stress that accompanies even everyday tasks such as homework can lead parents to question their child‐rearing abilities (Brinkman et al., ). A key factor in parents resorting to the use of medication for their child with ADHD is familial stress (Cormier, ). Another ramification of parental stress may be less display of warmth toward one's child (Bogels, Lehtonen, & Restifo, ).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of methodological consistency with the definitions of different family phenomena is problematic for family researchers and clinicians who are interested in replicating studies, performing systematic or integrative reviews, or translating research findings into practice. Only five studies explicitly used a theoretical framework or conceptual model to guide their work on family‐related phenomena (Conlon, Strassle, Vinh, & Trout, ; Cormier, ; Firmin & Phillips, ; Kendall, Leo, Perrin, & Hatton, ; Kendall & Shelton, ). The studies cited above were primarily qualitative in nature and used phenomenological approaches or grounded theory methods.…”
Section: Resultsmentioning
confidence: 99%
“…The second theme is that parenting practices and caregiver health influence the care and outcome of children with ADHD. In the descriptive studies, parental knowledge, perspectives, strategies, and decision making were important considerations for how ADHD treatment was perceived and delivered by families (Bussing, Schoenberg, & Perwien, ; Cormier, ; Firmin & Phillips, ; Olaniyan et al., ). These parenting practices were also present in the intervention studies where the combined treatment for ADHD (medication management and behavioral therapy) decreased negative or ineffective discipline and parenting practices (Hinshaw et al., ; Wells et al., ).…”
Section: Resultsmentioning
confidence: 99%